2015
DOI: 10.3390/ijerph120201773
|View full text |Cite
|
Sign up to set email alerts
|

Field Testing of Alternative Cookstove Performance in a Rural Setting of Western India

Abstract: Nearly three billion people use solid fuels for cooking and heating, which leads to extremely high levels of household air pollution and is a major cause of morbidity and mortality. Many stove manufacturers have developed alternative cookstoves (ACSs) that are aimed at reducing emissions and fuel consumption. Here, we tested a traditional clay chulha cookstove (TCS) and five commercially available ACSs, including both natural draft (Greenway Smart Stove, Envirofit PCS-1) and forced draft stoves (BioLite HomeSt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 30 publications
3
33
2
1
Order By: Relevance
“…63 On the other hand, larger-scale randomized interventions with controlled populations, similar to our study, have shown ND stoves do not consistently reduce HAP. 45, 46 The study's finding on Abs has important climate implications.…”
Section: Environmental Science and Technologymentioning
confidence: 54%
“…63 On the other hand, larger-scale randomized interventions with controlled populations, similar to our study, have shown ND stoves do not consistently reduce HAP. 45, 46 The study's finding on Abs has important climate implications.…”
Section: Environmental Science and Technologymentioning
confidence: 54%
“…If we assume the ventilation conditions to be typical of a traditional household, these findings suggest that ICS will generally perform worse in a field-based setting where ventilation conditions are uncontrolled. This is one of the reasons why field-based ICS measurements do not show the ability to reduce emissions to levels that may have some positive health benefits as suggested by lab based measurements (Muralidharan et al 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, field-based measurements suggest health benefits may not actually be as significant as those suggested from lab-based measurements (Muralidharan et al 2015; Roden et al 2009; Wathore et. al 2017), therefore expending more money for higher quality, yet still underperforming stoves, may not be the best first step toward intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Other forms of improved cook stoves have also been implemented. Although the use of these improved cook stoves helps reduce the particulate matter produced, this load remains well above the WHO safety limits 65 . An 85% reduced exposure to particulate matter is required to achieve a desired clinical effect.…”
Section: Interventionsmentioning
confidence: 97%